Cancer Screening Recommendations for Solid Organ Transplant Recipients: A Systematic Review of Clinical Practice Guidelines. Issue 1 (30th August 2016) - Acuna, S. A.; Huang, J. W.; Scott, A. L.; Micic, S.; Daly, C.; Brezden‐Masley, C.; Kim, S. J.; Baxter, N. N.
Abstract : Solid organ transplant recipients (SOTRs) are at increased risk of developing and dying from cancer. However, controversies exist around cancer screening in this population owing to reduced life expectancy and competing causes of death. This systematic review assesses the availability, quality and consistency of cancer screening recommendations in clinical practice guidelines (CPGs). We systematically searched bibliographic databases and gray literature to identify CPGs and assessed their quality using AGREE II. Recommendations were extracted along with their supporting evidence. Thirteen guidelines were included in the review. CPGs for kidney recipients were the most frequent source of screening recommendations, and recommendations for skin cancer screening were most frequently presented. Some screening recommendations differed from those for the general population, based on literature demonstrating higher cancer incidence among SOTRs versus direct evidence of screening effectiveness. Relevant stakeholders such as oncology specialists, primary care providers and public health experts were not involved in the formulation of the screening recommendations. In conclusion, although several guidelines make recommendations for cancer screening in SOTRs, the availability of cancer screening recommendations varied considerably by transplanted organ. More studies are required to inform cancer screening recommendations in SOTRs, and guideline development should involve transplant patients, oncologists and cancer screening specialists. Abstract : This systematic review assesses cancer screening recommendations in posttransplant care clinical practice guidelines and finds that although 13 guidelines make recommendations for cancer screening in transplant recipients, the availability of recommendations varies considerably by transplanted organ and that relevant stakeholders were not involved in the formulation of screening recommendations. See Blosser's editorial onpage 9 .